The Local Wisdom Story to Teach Extensive Reading on Fiction - Astried Damayanti; Yudi Basuki; Dwi Putri Hartiningsari (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2024)
The research is intended to apply local wisdom story in reading learning. Local wisdom nowadays is one of recommended material to teach many subjects such as in reading subject. The research was conducted for third semester students of English Language Education Study Program of STKIP PGRI Trenggalek who were joining Extensive Reading on Fiction. Local wisdom story was used as material in learning. Qualitative research was used in the research. The students were assigned to comprehend the local wisdom story and analyzed it based on several components, such as the point of view, character’s traits, the role of each character and character based on the function and types. To know the students’ responses, questionnaire about the implementation of local wisdom story was distributed. The result of questionnaire showed that the student gave good and positive responses about the implementation of local wisdom story in learning Extensive Reading on Fiction class. They stated that the story given was interesting and attracted them to analyze some components of it.